Qualitative health research creating a new discipline - Morse, Janice M. (Walnut Creek, Calif. : Left Coast Press, 2012)
"The leading figure in qualitative health research (QHR), Janice M. Morse, asserts that QHR is its own separate discipline--distinct from both traditional health research and other kinds of qualitative research--and examines the implications of this position for theory, research, and practice. She contends that the health care environments transform many of the traditional norms of qualitative research and shape a new and different kind of research tradition. Similarly, the humanizing ethos of qualitative health research has much to teach traditional researchers and practitioners in health disciplines. She explores how the discipline of QHR can play out in practice, both in the clinic and in the classroom, in North America and around the world. A challenging, thought-provoking call to rethink how to conduct qualitative research in health settings"--Provided by publisher.
Machine generated contents note: Preface Chapter 1: What is Qualitative Health Research? Chapter 2. Role of QHR in Humanizing health care Chapter 3. Methodological contribution of QHR to qualitative research. Chapter 4: Compelling evidence: Expanding criteria? Chapter 5: Do we have a subdiscipline? Chapter 6: Champion QHR Chapter 7: QHR: A global change for humanizing health care Notes References Index About the Author.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Medical care -- Research; Qualitative research; Electronic books